PEMANFAATAN MEDIA PEMBELAJARAN OLEH GURU GEOGRAFI SEKOLAH MENENGAH ATAS DI KOTA BARABAI KABUPATEN HULU SUNGAI TENGAH - Yuliana Yuliana (Universitas Lambung Mangkurat, 2013)
The use of media in teaching and learning process can help the smoothness, effectiveness, and the efficiency in reaching the learning objective. The use of teaching media in eleventh grade of Social studies based on the syllabus of BSNP for Senior High School in Barabai Hulu Sungai Tengah Regency was not optimal, about 33,84% was not implemented. To reveal the cause was not optimal utilization of instructional media in class XI IPS high schools in the city Barabai Hulu Sungai Tengah. The study was designed with a descriptive design and implemented in senior high schools Barabi Cities Hulu Sungai Tengah. There are 3 schools with four teachers who teach geography class XI IPS is used as a source of research data. The research results, it was found that (1) the availability of the teaching media for Geography in the eleventh grade of Senior High School in Barabai Hulu Sungai Tengah regency was not complete (2) The teaching media for Geography in the eleventh grade of Senior High School in Barabai Hulu Sungai Tengah regency was not used optimaly based on BSNP. (3) The teachers' habit in teaching the eleventh grade student of Senior High School in Barabai Hulu Sungai Tengah Regency was to only use the textbook as the teaching media; and (4) The teachers were not skilled enough in using the teaching media in the eleventh grade of Senior High School in Barabai Hulu Sungai Tengah Regency. There are some suggestions proposed to make the use of teaching media optimally.Key words: Geography teacher, and learning media